Acute eosinophilic pneumonia following electronic cigarette use. (2019) - Arter, Zhaohui L.; Wiggins, Amanda; Hudspath, Caleb; Kisling, Adam; Hostler, David C.; Hostler, Jordanna M.
Abstract: Electronic cigarette (e-cigarette) use, or vaping, is gaining widespread popularity among adults aged 18–35. Vaping is commercially promoted as a safer alternative to traditional cigarette smoking. Previous studies have reported a close relationship between conventional cigarette smoking and acute eosinophilic pneumonia (AEP), but only one case report to date associates vaping with AEP in a male patient. We present the first case of AEP involving a young female after use of e-cigarettes. Clinicians should consider AEP when evaluating young patients with hypoxic respiratory failure and a recent history of e-cigarette use. This case highlights the need for more research into the relationship between e-cigarettes and AEP.